Fish assemblages associated with Egeria in a tropical reservoir: investigating the effects of plant biomass and diel period - PELICICE, F.M.; AGOSTINHO, A.A.; THOMAZ, S.M. (2018)
PELICICE, Fernando Mayer; AGOSTINHO, Angelo Antonio; THOMAZ, Sidinei Magela. Fish assemblages associated with Egeria in a tropical reservoir: investigating the effects of plant biomass and diel period. Acta Oecologica, Paris, v.27, no.1, p.9-16, 2005.